Model Pengelolaan Agrowisata Yang Terintegrasi Dengan Wisata Rohani Salib Kasih Di Tarutung - Dharma Putera Simanungkalit; Agus Purwoko; T. Alief Aththoric (Fakultas Teknik, 2020)
Salib Kasih is located in the pine forest area has been made an icon of the city of Tarutung as a religious tourism destinations that visited by many tourists. Geographically, this area has a landscape with a distinctive panorama of fresh pine forests and agricultural cultivation land. The area has great potential in sustainable agro-tourism management and can increase Local Government Revenue (PAD). However although, this potential has not been exploited as one of the agro tourism management models that is integrated with the religious history destination of the Salib Kasih. This study aimed to develop an agritourist management model by analyzing the needs of facilities and infrastructure that are integrated with religious tourism in Salib Kasih area’s. Based on the results of the research and discussion, it can be concluded there are some alternative agrotourism management models which integrated the religious tourism of Salib Kasih area’s by paying attention to the local wisdom, cultivation product, cattle farm, and bee keeping.